Kalman–Bucy filter-based tracking controller design and experimental validations for a quadcopter with parametric uncertainties and disturbances. Issue 1 (2nd January 2023) - Zhu, Xuan-Zhi; Cabecinhas, David; Xie, Wei; Casau, Pedro; Silvestre, Carlos; Batista, Pedro; Oliveira, Paulo
Abstract : This paper addresses the problem of trajectory tracking for a quadcopter subject to parametric uncertainties and disturbances. Using the backstepping technique and ignoring parametric uncertainties and disturbances, a nominal controller is proposed for the quadcopter. In order to ensure that the controller is adaptive to parametric uncertainties (i.e. unknown but constant mass and tensor of inertia) and external disturbances, an exponentially stable estimator is designed based on the Kalman–Bucy filter. The closed-loop system resulting from the interconnection of the plant, the controller, and the estimator is such that the backstepping error is uniformly ultimately bounded. Furthermore, simulation and experimental results are presented, validating the stability and robustness properties of the proposed control strategy.